Cognitive decline complaints scale (CDCS): validation and normative studies for the adults and older adults Portuguese population - Frias, Joana Rita (2022)
Objectives: Subjective Cognitive Complaints, which result from the self-perception of Subjective Cognitive Decline, are frequently reported by older adults. The Cognitive Decline Complaints Scale (CDCS) assesses subjective complaints of cognitive decline in several cognitive domains through three levels of severity. This study aims to psychometrically validate this instrument considering the Classical Test Theory, and to establish preliminary normative data of the CDCS for adults and older adults of the Portuguese population. Methods: The community-based sample consisted of 199 cognitively healthy Portuguese participants, aged 50 years or older, stratified according to several sociodemographic variables. In addition to the CDCS, all participants responded to an extensive neuropsychological assessment protocol. Results: The psychometric characteristics of the CDCS were generally adequate for this community sample (e.g. Cronbach's alpha = .936). As for the sociodemographic variables analyzed, only the geographic region showed differences in the CDCS scores, which were more significant in the Azores. There were no significant correlations or differences between the CDCS scores and age and educational level and, therefore, normative data were explored considering the total sample. Conclusion: As a scale, the CDCS allows for the detailed assessment of subjective cognitive complaints and the determination of whether or not such complaints are considered normative, which will facilitate an empirically based understanding of this dimension of psychological functioning and also provide indications as to the need for a more extensive neuropsychological assessment.